The treatment and diagnosis of ectopic eruption of the first permanent molar - DU Qin; YANG Yifan; JIA Shuxian; LI Xiaobing (口腔疾病防治, 2023)
Ectopic eruption of the first permanent molar is a common malocclusion in the early stage of mixed dentition. The incidence among children aged 6-10 years is 0.83%-8.7%, with an increasing trend. The main manifestation is mesial impaction of the first permanent molar during eruption, which is accompanied by the loss of root resorption and space loss of the second primary molar. Ectopic eruption of the first permanent molars can lead to underdevelopment of the dental arch and severe crowding of the posterior dentition. Prevention and early intervention are very important. The ectopic eruption of the first permanent molar is related to the disruption of the differential growth and developmental balance among the teeth, alveolar bone and jaw. In clinical practice, the diagnosis can be made according to the patient's medical history and clinical and imaging examinations, and the treatment can be performed by dividing the teeth, dividing the distal slices of the second primary molars, and distally moving the first permanent molars. This paper reviews the incidence, etiology, clinical manifestations, risks of ectopic eruption of the first permanent molar, diagnostic methods, and common treatment options to provide references for clinical treatment.